Francisco Leocata and his interpretation of the cogito (Tábano, 2024)
This article analyzes Leocata’s vision of the Cartesian cogito. His reading of the sum from the act of being of St. Thomas’ creationism and its greater evidence for the human intellect is highlighted, as well as a new version of the “idea of infinite being” that leads to a new reconsideration of Descartes’ ontological argument. It concludes with a call for debate on this re-reading.
Keywords: Act of being; Idea of Infinite Being; Ontological Argument; Participation; Cogito